Core Ethical Values Pendidikan Karakter Berdasarkan Sumber Nilai Ajaran Islam - Siti Nurmela; Hobir Asyari; Aan Hasanah; Bambang Samsul Arifin (Departement of Mathematics Education, 2024)
This research is qualitative research using a library study method from various trusted references such as reputable journals, results of scientific conferences, and various other sources, and of course from the main sources of Islamic teachings, namely the Al-Qur'an and Hadith. The aim of this research is to examine and describe the core values ​​of character education based on Islamic teaching sources. The research results explain that in QS. Verse An-Nisa 9 explains the command to look after generations and not leave behind weak generations. Humans are born in a state of nature, but often due to human actions that nature changes, both due to internal and external factors. Therefore, the application of the core values ​​of character education which originate from Islamic teachings is very necessary so that students can consistently implement them in their daily lives. The core values ​​of character education based on Islamic teaching sources include character towards God Almighty, character towards oneself, character towards fellow humans, character towards the environment, character towards the nation, and other good characters completely and authentically to be applied in life. The results of this research also explain how core values ​​originating from Islamic teachings are internalized, assimilated and applied in educational character to maintain human nature and become the khaira of the ummah.